Isolated Polycystic Liver Disease: An Unusual Cause of Recurrent Variceal Bleed. (4th June 2018) - Khan, Mohammad Saud; Khan, Zubair; Javaid, Toseef; Akhtar, Jamal; Moustafa, Abdelmoniem; Lal, Amos; Tiwari, Abhinav; Taleb, Mohammad
Abstract : Isolated polycystic liver disease is a rare disorder. Majority of the patients with isolated polycystic liver disease are asymptomatic with incidental detection of liver cysts on imaging studies done for other purposes. Minority of patients develop symptoms which are mostly secondary to enlarging cysts size and hepatomegaly. Rarely, these patients develop portal hypertension and can present with its clinical manifestations and consequences in the form acute variceal bleeding or recurrent ascites. We present a rare case of 67-year-old female patient with significant history of polycystic liver disease who presented to the hospital with recurrent hematemesis and melena. She underwent esophagogastroduodenoscopy which showed multiple large esophageal varices requiring banding.